Analisis Kandungan Kadmium (Cd), Seng (Zn), dan Mangan (Mn) pada Buah Stroberi (Fragaria × ananassa) serta Karakterisasi Ketersediaan Hayati Logam di Tanah Vulkanik Pertanian Sembalun - Herry Abdullah; Irman Supryandi; Khairul Fuad (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aimed to determine the concentrations of cadmium (Cd), zinc (Zn), and manganese (Mn) in strawberry fruits (Fragaria × ananassa) and to characterize the bioavailability of these metals in volcanic soils from a major strawberry-growing area in Sembalun, Lombok Island, Indonesia. Fruit and soil samples were collected from five cultivation sites representing local agroecological variability. Metal concentrations were analyzed using Atomic Absorption Spectrophotometry (AAS) following wet digestion, while soil metal bioavailability was assessed using the DTPA extraction method. Supporting soil chemical properties, including pH and organic matter content, were also measured to aid interpretation. The results indicated that Cd concentrations in strawberry fruits were low and did not exceed internationally recommended maximum limits, whereas Zn and Mn were detected within ranges commonly reported for horticultural crops. Volcanic soils from Sembalun exhibited relatively low Cd-DTPA fractions compared with Zn and Mn. Pearson correlation analysis revealed positive relationships between DTPA-extractable Zn and Mn in soils and their corresponding concentrations in fruits, while Cd accumulation appeared more strongly influenced by variations in soil chemical conditions. Overall, these findings suggest that metal bioavailability, particularly for essential micronutrients, plays an important role in controlling metal accumulation in strawberry fruits grown on volcanic soils. This study provides a scientific basis for soil quality evaluation and for the monitoring of strawberry production systems in volcanic agricultural environments, while acknowledging the spatial and temporal limitations of the present investigation.